The efficacy and associated bleeding complications of recombinant antithrombin supplementation among intensive care unit patients. Issue 157 (September 2017) - Koami, Hiroyuki; Sakamoto, Yuichiro; Sakurai, Ryota; Ohta, Miho; Imahase, Hisashi; Yahata, Mayuko; Umeka, Mitsuru; Miike, Toru; Nagashima, Futoshi; Iwamura, Takashi; Yamada, Kosuke Chris; Inoue, Satoshi
Abstract: Introduction: The aim of this study was to evaluate the efficacy and complications of recombinant antithrombin (rAT) supplementation for adult patients with disseminated intravascular coagulation (DIC) compared with conventional plasma derived AT (pAT) treatment in the intensive care unit. Materials and methods: This study was performed in a single national university hospital in Japan. Adult patients from April 2015 to March 2016 with DIC were divided into two groups based on the type of AT agent used: the pAT group (n = 24) and the rAT group (n = 21). Patient demographics, medical history, diagnosis, blood tests, various clinical scores, AT activity, complications, and clinical outcome were collected and analyzed retrospectively. Results: Significantly higher SIRS and APACHEII scores were confirmed in the rAT group than the pAT group. The initial dose of AT was significantly higher in the rAT group than in the pAT group. ATIII values before and after initial supplementation and during their ten-day clinical course were statistically similar between two groups. During the same period, 10 bleeding adverse events were found and there was no significant difference between both groups. Significantly more cases of the rAT group were administered with recombinant thrombomodulin concomitantly than those of the pAT group. Despite significantly more severe patients in rAT group, the clinical outcomes were the same in each group. Conclusions: Compared with pAT, the supplementation of rAT indicates clinical effectiveness without increasing the risk of bleeding complications in adult DIC patients with low AT activity. Highlights: Efficacy of rAT agent in adult DIC patients with low AT value was evaluated. Despite more severe in rAT group, the clinical outcomes were equal within groups. Administration of rAT didn't increase the risk of bleeding complication.